If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying n + (-12) = 3n n + -12 = 3n Reorder the terms: -12 + n = 3n Solving -12 + n = 3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-3n' to each side of the equation. -12 + n + -3n = 3n + -3n Combine like terms: n + -3n = -2n -12 + -2n = 3n + -3n Combine like terms: 3n + -3n = 0 -12 + -2n = 0 Add '12' to each side of the equation. -12 + 12 + -2n = 0 + 12 Combine like terms: -12 + 12 = 0 0 + -2n = 0 + 12 -2n = 0 + 12 Combine like terms: 0 + 12 = 12 -2n = 12 Divide each side by '-2'. n = -6 Simplifying n = -6
| X-2x+3=4x+2 | | 9x-9=9-8x | | 8x-16-2x=34 | | 12ab-28bc+20ac=0 | | x^(2/#)=1/3 | | 10x=0.000001 | | 3t^2-16t+21=0 | | -2x-6y+11=-11 | | 4n+21=-3 | | q^2+75q-6250=p | | q^2+75q-6250=q | | 4n^2-x-2000=0 | | 2x^2+6x-77=0 | | -3=6-x/9=3 | | -16times-0.15=x | | 6b(2a-3c)-5d(2a-3c)=0 | | 6(3s+6)=216 | | X-17=x+51 | | 3(x+10)=(2x+30) | | -16x-0.15=f | | 4(2l+5)=92 | | q^2+75q-6250=0 | | 0.51(2x)=x+1 | | (2x-1)(3x-1)=(6x+2)(x-4) | | 2x-9/5=x+18 | | g^2*10g^3-2g^3+g^5=0 | | 6x^2-x-1000=0 | | 5(a-5)=80 | | 3x+10=x+17 | | (7x-84)/(14X) | | 3x+6ax=0 | | 5/4y=12 |